Don't call it quits turn the job you have into the job you love - Gaynor, Shana Lebowitz (New York McGraw Hill, 2022)
"Why don't you just quit?" If you're unfulfilled by your job, you've likely been asked this question before. But the truth is, it's not always necessary or even advisable to make a career change in order to enjoy work more. For those who can't reasonably leave a stable position right now and for anyone who wants to feel happier at work Don't Call It Quits is essential reading"--
Includes bibliographical references and index.
Keywords: Career changes; Job satisfaction; Quality of work life